Functional analysis of cancer-causing FBXW7 mutations - Davis, HL (2012)
FBXW7 encodes the substrate recognition component of an SCF E3 ubiquitin ligase complex. This complex regulates the degradation of multiple targets, such as Notch1, c-Jun, c-Myc and cyclin E, that function in critical developmental and cancer pathways. FBXW7 mutations are found in cancers of diverse tissue origins, with one of the highest mutation rates in the colorectrum. FBXW7 mutations are typically missense mutations that disrupt the substrate recognition domain at critical arginine propellor-tips. Mutations are often mono-allelic suggesting that FBXW7 is not a typical tumour supressor gene. Despite this, most of the evidence on FBXW7 function to date comes from null systems. Several Fbxw7 -null mouse models have been generated and suffer homozygous embryonic lethality due to disrupted vascular development. Conditional Fbxw7-null mice have been created but do not in general reflect the mutation spectrum found in human tumours. In order to analyse the functional effects of Fbxw7 propellor-tip missense mutations, mice carrying a commonly-occurring Fbxw7 R482Q mutation were generated. This propellor-tip mutation was knocked-in constitutively and whilst heterozygous mice developed normally in utero, they died perinatally due to defective lung development. Cleft palate and eyelid fusion defects were also observed with incomplete penetrance. Fbxw7 substrates were screened in embryonic lungs and significantly elevated protein levels of Klf5 and Tgif1 were observed. The Fbxw7 R482Q mutation was also conditionally knocked-in in the gut. In the heterozygous state, large adenomas in the small intestine were observed at a low multiplicity, in approximately 30% of mice at an age greater than 300 days. Upregulation of Wnt signalling and Ctnnb1 mutations have been identified in a selection of these tumours. Breeding the Fbxw7R482Q allele onto Apc-mutant backgrounds led to accelerated morbidity, in which compound R482Q/Apc-mutant mice exhibited polyps of increased number and size. Elevated protein levels of Fbxw7 substrates Klf5 and Tgif1 were observed in adenoma and normal intestinal tissue from these mice. In vitro work using epitope-tagged murine wildtype and propellor-tip mutant Fbxw7 proteins showed that they were capable of dimerising, opening the prospect of investigating a dominant negative mechanism of action. To conclude, an Fbxw7 propellor-tip mutation studied in vivo resulted in both disrupted embryonic development and intestinal tumorigenesis and was distinct from Fbxw7 -null alleles.